Monitoring development financing: A first assessment of the 2018 reform one more effort? - Serge Tomasi (Fondation pour les études et recherches sur le développement international (FERDI), 2024)
The reform of official development assistance (ODA) accounting implemented from 2018, combined with the creation of Total Official Support for Sustainable Development (TOSSD), represents a substantial improvement in the monitoring of development financing. In some respects, however, it remains in the middle of the road, and there is still room for improvement.
Keywords: 330; Developing countries; Least developed Countries (LDCs); Development financing; Official Development Assistance (ODA)